The Influence of Celebrity Endorsers, Live Streaming and Online Customer Reviews on Consumer Purchasing Decisions Somethinc Products on Tiktok Shop in Yogyakarta - Lestari, Lyssia Putri; Widarta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of Celebrity Endorser, Live Streaming, and Online Customers Review on Purchasing Decisions for Somethinc Products at TikTok Shop. The sample consisted of 385 respondents who had purchased the product. Data was collected through a survey using a questionnaire, and proved to be valid and reliable. The Classical Assumption Test shows that the data is normally distributed and the regression model is free from multicollinearity and heteroscedasticity problems. The results showed that Celebrity Endorser, Live Streaming, and Online Customers Review each, as well as simultaneously, have a significant effect on Purchasing Decision. The findings imply the importance of strengthening those strategies for manufacturers to strengthen their marketing position on TikTok Shop.